Elucidation of potential anticancer, antioxidant and antimicrobial properties of some new triazole compounds bearing pyridine-4-yl moiety and cyclobutane ring - Koparir, Pelin; Parlak, Akif Evren; Karatepe, Arzu; Omar, Rebaz A. (Elsevier, 2022)
Thiosemicarbazides (2a-e) were obtained by the interaction of pyridine-4-carboxylic acid hydrazide (1) with five different isothiocyanate (RNCS) derivatives. By addition of KOH to the reaction medium, ethyl, allyl, phenyl and benzyl, p-tolyl substituted 1,2,4-triazoles (3a-e) were obtained. 3a-e were dissolved in dry acetone containing K2CO3 in the presence of 2-chloro-1-(3-methyl-3- mesitylcyclobutyl) ethanone (4) to give 3,4,5-trisubstituted 1,2,4-triazole sulfanyl compounds containing a cyclobutane ring (5a-e). The structures of the final compounds were confirmed by elemental analyses, FT-IR, H-1 NMR and C-13 NMR. Due to many activities regarding pharmacology, Compounds such as 1,2,4-triazole attract high attention in the fields of chemistry, pharmacology, and biology. All the newly synthesised compounds were screened for their Antioxidant, antimicrobial, anti-cancer activities. The measurement of the antioxidant feature of the compounds was performed by DPPH radical scavenging activity technique. It was observed that the activity of some of the compounds was close to the standard antioxidant BHT. Furthermore, the anticancer effects of compounds were investigated against HT29 human colon adenocarcinoma cells. It has been noted that all -compounds inhibited cancerous cells in a statistically significant compared to the control. For the measurement of antimicrobial activity Agar well diffusion method was preferred. For the antimicrobial study, S. aureus, E. faecalis, P. aeruginosa, E. coli, and a single fungi C. albicans have been used. They could also be stated as ATCC 29213, 29212, 27853, 2592, and 10231 respectively. The resulting range of MIC values for the chemicals was between 15.625 - >125 mu M. In conclusion; all compounds have shown various and important bioactivities at different levels, such as being antioxidant, antimicrobial, and anticancer. (C) 2022 The Author(s). Published by Elsevier B.V. on behalf of King Saud University.
Keywords: 1,2,4-Triazole; Anticancer; Antioxidant; Antimicrobial; Biological activities